Clinical and genetic features of congenital bile acid synthesis defect with a novel mutation in AKR1D1 gene sequencing: Case reports. Issue 25 (24th June 2022) - Pham, Anh-Hoa Nguyen; Thi, Kim-Oanh Bui; Thi, Mai-Huong Nguyen; Ngo, Diem-Ngoc; Naritaka, Nakayuki; Nittono, Hiroshi; Hayashi, Hisamitsu; Dao, Trang Thi; Nguyen, Kim-Huong Thi; Nguyen, Hoai-Nghia; Giang, Hoa; Tang, Hung-Sang; et al.
Abstract: Rationale: Congenital bile acid synthesis defect (BASD) is a rare disease caused by mutations in the aldo-keto reductase 1D1 gene, which encodes the primary Δ4-3-oxosteroid 5β-reductase enzyme. Early disease diagnosis is critical for early treatment with bile acid replacement therapy, with an excellent chance for recovery. In contrast, protracted diagnosis and treatment may lead to poor outcomes, including decompensated hepatic cirrhosis, liver transplant, and even death. Patient concerns: Three clinical congenital bile acid synthesis defect cases in the Vietnamese population are herein reported. These pediatric patients presented with symptoms of prolonged postpartum jaundice and abnormal loose stool (mucus, lipids, and white). The clinical examinations showed hepatosplenomegaly. Urinalysis showed a very low fraction of primary bile acids and atypical 3-oxo-Δ4- bile acids in all three patients. Diagnoses: The patients were diagnosed with primary Δ4-3-oxosteroid 5β-reductase deficiency. Next-generation gene sequencing revealed two homozygous mutations in the aldo-keto reductase family 1 member D1 gene. The first is a documented variant, c.797G>A (p.Arg266Gln), and the second is a novel mutation at c.155T>C (p.Ile52Thr). Interventions: Immediately after diagnosis, patients were treated with oral chenodeoxycholate 5 mg/kg/d. Outcomes: The patients' symptoms, signs, and primary bile acids levels improved significantly. Lessons: Clinicians should consider genetic disorders related to cholestasis for effective and life-saving treatment. A prompt genetic analysis by next-generation gene sequencing enables patients to access bile acid replacement therapy earlier, significantly improving short- and long-term outcomes.